Dental Students Knowledge in Colour Determinationaccuracy of Fixed Partial Denture in RSGM Usu - Thevaraj A L Vigneswaran; Ika Andryas (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The aesthetics of fixed denture treatments are important factors that determine the success of the treatment. The optimal esthetic results in the manufacture of crowns and bridges require several considerations such as the size, shape, and color of the denture. The right color is one of the factors that influence the success of fixed bridges (GTJ) from an aesthetic aspect. In this descriptive survey research, the author examined the color of the ceramic metal that would be attached to the patient and compared it to the color guide and then the author distributed a questionnaire to assess the level of knowledge from clinical clerkship students at Prosthodontics Department Universitas Sumatera Utara regarding the procedure in determining the color of dentures. A colorimeter is used as a tool in determining the color accuracy of fixed dentures. The mean difference in color between the fixed denture and the color guide was tabulated and univariate analysis was performed. The results showed no significant color difference between the fixed denture and the color guide. 80,95% of respondents had a good knowledge level in the determining color procedure.